Balloon-Anchored CoKatte® for Successfully Delivering Balloons for an Occluded Anomalous Right Coronary Artery - Araki, Makoto; Hikita, Hiroyuki; Hishikari, Keiichi; Takahashi, Atsushi (International Journal of Angiology, 2018)
Percutaneous coronary intervention (PCI) for anomalous right coronary artery (RCA), originating from the left coronary cusp is challenging, because of the difficulty in engaging the guiding catheter coaxially, and delivering balloons and stents. A 65-year-old man with effort angina underwent PCI for anomalous RCA. This report describes the method we used. Although, delivering the balloon was difficult in short of the guiding catheter's backup force, we finally succeeded by using one more guiding catheter and the balloon-anchored CoKatte®, a novel, straight 4.5-French child catheter, to strengthen the backup force.
Keywords: percutaneous coronary intervention; coronary vessel anomalies; case study; coronary occlusion; CoKatte®; CTO